Pengaruh Terpaan Konten Politik Instagram @bijakmemilih.id Terhadap Minat Memilih di Pemilu 2024 - Mujiarto, Calysta Amelia; Simamora, Fidelia; Naila Almaida (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2024)
Data from the Kominfo RI notes that Instagram is in third place with 148 hoax contents. The @bijakmemilih.id Instagram account presents content about elections from a neutral, objective, and interestingly packaged side to target novice voters. This research is interesting to find out whether or not there is an influence from the exposure of @bijakmemilih.id content on the interest in voting for novice voters and senior voters. Respondents of this study totaled 100 and were samples taken from the population of Instagram followers @bijakmemilih.id. This research uses the Elaboration Likelihood Model theory with a quantitative approach and survey method. Based on 100 answers, the results show that novice voters and senior voters are influenced by the exposure of @bijakmemilih.id content so that they have an interest in voting in the 2024 election, the message is received through the central route.